Implementasi Kemampuan Berpikir Kritis Anak Usia Dini Melalui Eksperimen Lilin Uap Di Raudhatul Athfal - Nurhidaya, Andi Rezky; Naba, Abdul Hakim; Ruswiyani, Endang; Nirwana, Nirwana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
This study aims to evaluate the effectiveness of vapor candle experiments in improving critical thinking skills in early childhood at RA Mardhati, Makassar. Early childhood education plays an important role in children's cognitive, social and emotional development. Critical thinking skills, such as analysis and problem solving, need to be developed early on. Based on observations at RA Mardhati, the critical thinking skills of group A children are still less than optimal, so a more interactive learning method is needed. The steam candle experiment was chosen because it allows children to observe the physical changes of the candle, stimulating them to ask questions, make hypotheses, and analyze the results. This research used descriptive qualitative method with observation, interview, and documentation techniques. Data analysis was conducted through data reduction, presentation, verification, and triangulation. The results showed that the vapor candle experiment effectively improved children's critical thinking skills. Of the 15 participants, 70% experienced significant improvement, with 47.33% in the Developing As Expected (BSH) category and 24.33% Developing Very Well (BSB). The experiment not only improved cognitive skills but also introduced a spiritual dimension by linking natural phenomena, making a significant contribution to science-based learning methods in ECD.